2020
DOI: 10.1111/myc.13084
|View full text |Cite
|
Sign up to set email alerts
|

Posaconazole delayed‐release tablets in paediatric haematology–oncology patients

Abstract: | INTRODUC TI ONInvasive fungal infections (IFIs) represent a major cause of morbidity and mortality in high-risk paediatric haematology-oncology patients. [1][2][3] Posaconazole is a broad-spectrum triazole approved for patients ≥13 years (≥18 years in Europe) as oral and intravenous formulation. Two oral formulations are approved: suspension and tablet. The oral suspension has a variable bioavailability depending on gastric pH and the type of concomitant meal. 4,5 Differently from suspension, Summary Backgro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…8,186 Therefore, TDM is indicated for patient groups at risk of low exposure who are receiving prophylaxis with the new posaconazole tablet formulation (e.g. patients with cystic fibrosis, 187 presence of graft-versus-host disease, 10,181 drug-drug interactions including those on concurrent corticosteroids and proton pump inhibitors, 10,188 obese patients, 189,190 young children [191][192][193][194] and patients with gastrointestinal complications including diarrhoea 10,190,195,196 ).…”
Section: Question 2 What Are the Present Antifungal Tdm Targets Sampling And Sample Type Time-to-resampling And Dose Adjustment?mentioning
confidence: 99%
“…8,186 Therefore, TDM is indicated for patient groups at risk of low exposure who are receiving prophylaxis with the new posaconazole tablet formulation (e.g. patients with cystic fibrosis, 187 presence of graft-versus-host disease, 10,181 drug-drug interactions including those on concurrent corticosteroids and proton pump inhibitors, 10,188 obese patients, 189,190 young children [191][192][193][194] and patients with gastrointestinal complications including diarrhoea 10,190,195,196 ).…”
Section: Question 2 What Are the Present Antifungal Tdm Targets Sampling And Sample Type Time-to-resampling And Dose Adjustment?mentioning
confidence: 99%
“…For an invasive infection, rapid attainment of the PK/PD target is warranted, thereby favoring the use of the tablet or intravenous formulation. 7,42,43 Population modeling of a larger dataset, including rich sampling and including patients administered different formulations, is required to achieve well-informed dose-finding for immunocompromised children.…”
Section: Discussionmentioning
confidence: 99%
“…In keeping with the adult literature, the administration of posaconazole modified-release tablets is associated with superior attainment of therapeutic levels in children compared to oral suspension. 100,116,[158][159][160] Attainment of target level (>700 ng/mL) in 94% (32/34) of children receiving modified-release tablets using weight-banded dosing has been reported (Table 7). 116 In two small studies of IV posaconazole for IFD prophylaxis, attainment of target levels was reported in 95-100% of children using doses of 6-7 mg/kg/day.…”
Section: Posaconazole: Tablet and Intravenous Formulation In Childrenmentioning
confidence: 99%